Stroke-induced immunosuppression and poststroke infection. Issue 1 (12th January 2018) - Shi, Kaibin; Wood, Kristofer; Shi, Fu-Dong; Wang, Xiaoying; Liu, Qiang
Abstract : Infections occur commonly after stroke and are strongly associated with an unfavourable functional outcome of these patients. Approaches for effective management of poststroke infection remain scarce, presenting an urgent need for preventive anti-infection strategies for patients who have suffered a stroke. Emerging evidence indicates that stroke impairs systemic immune responses and increases the susceptibility to infections, suggesting that the modification of impaired immune defence could be beneficial. In this review, we summarised previous attempts to prevent poststroke infections using prophylactic antibiotics and the current understanding of stroke-induced immunosuppression. Further elucidation of the immune mechanisms of stroke will pave the way to tailored design of new treatment to combat poststroke infection via modifying the immune system.